DNA Variations between Medicago truncatula Symbiotic Mutant Line and Native Variant Using Fluorescence-Based AFLP Marker - Asmaa Hamdy Hassan; Ghada Abu El-Heba; Mohamed A-bouzeid (Highlights in BioScience, 2020)
Abstract